Analysis of molecular characteristics of CAMP-negative Streptococcus agalactiae strains - Zhou, Jie; Zhang, Li; Zhang, Yang; Liu, Hui; Xu, Kangli; Zhang, Baohu; Feng, Tianyuan; Yang, Shucai (Frontiers in Microbiology, 2023)
Background: Streptococcus agalactiae can produce CAMP factor, which can promote the β-hemolysin activity of Staphylococcus aureus, forming an arrow-shaped hemolysis enhancement zone at the intersection of the two bacterial species on a blood agar plate. This characteristic feature of Streptococcus agalactiae has led to the widespread use of the CAMP test as an identification method. Methods: Vaginal/rectal swabs, collected from women at 35-37 weeks of pregnancy, were first inoculated into a selective enrichment broth media, then subcultured onto GBS chromogenic agar and 5% sheep blood agar sequentially. The VITEK-2 automatic identification system and MALDI-TOF MS were initially employed for identification, followed by the CAMP test. CAMP-negative strains underwent 16S rDNA and cfb gene sequence analysis, as well as bacterial multilocus sequence typing. Results: A total of 190 strains were isolated, with 15 identified as CAMP-negative. Further 16S rDNA gene sequence analysis confirmed that all 15 strains were Streptococcus agalactiae. The MLST typing assay revealed that these 15 strains were of the ST862 type. The cfb gene was amplified and electrophoresed, but no specific fragments were found, indicating that these strains lack the CAMP factor due to cfb gene deletion. Antibiotic susceptibility tests demonstrated no resistance to penicillin, ampicillin, vancomycin and linezolid among the GBS strains. However, there are significant differences in resistance rates to tetracycline. Conclusion: This study found that 7.9% of GBS strains isolated from the vagina/rectum of pregnant women were CAMP-negative, suggesting that the CAMP test method and primers targeting the cfb gene should not be used as the sole presumptive tests for GBS identification.